PERJANJIAN PERKAWINAN DALAM PERKAWINAN PADA GELAHANG - Mantra, I Gede; Januariawan, I Gede; Yanti, Ni Putu Linda Mega (VYAVAHARA DUTA, 2020)
Marriage â€œpada gelahangâ€ is an alternative form of marriage chosen by both parties of the prospective husband and family, considering that both the male family and the family of the woman are basically equally an only child.This type of research in this study is a type of normative hokum research or doctrinal research namely "research that uses library material or secondary data consisting of primary hokum material, secondary hokum material, and tertiary hokum material as the main data" (Soekanto and Mamudji, 2006 : 13). That is, by reviewing the books, articles and laws related to the marriage agreement. This research uses qualitative analysis by explaining the data that exists not in the form of numbers.Seeing the problems in marriage on the bracelet is very likely to occur during the marriage in gelahang. To avoid the ineptness of both parties it is necessary to anticipate early on by making marriage agreements. The marriage agreement governs the rights and obligations of both spouses, which must be performed during the term of marriage.Keywords: Marriage covenant, marriage on gelahang